2015
DOI: 10.3390/rs70201736
|View full text |Cite
|
Sign up to set email alerts
|

Time Series Analysis of Landslide Dynamics Using an Unmanned Aerial Vehicle (UAV)

Abstract: Abstract:In this study, we used an Unmanned Aerial Vehicle (UAV) to collect a time series of high-resolution images over four years at seven epochs to assess landslide dynamics. Structure from Motion (SfM) was applied to create Digital Surface Models (DSMs) of the landslide surface with an accuracy of 4-5 cm in the horizontal and 3-4 cm in the vertical direction. The accuracy of the co-registration of subsequent DSMs was checked and corrected based on comparing non-active areas of the landslide, which minimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
260
0
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(277 citation statements)
references
References 21 publications
6
260
0
11
Order By: Relevance
“…This topic has been described by several authors (Dewitte et al, 2008;Turner and Lucieer, 2013;Travelletti et al, 2012;Lucieer et al 2014a;Turner et al, 2015;Marek et al, 2015;Lindner et al, 2016;Peppa et al, 2017). In these works, numerous techniques based on the multi-temporal comparison of RPAS data sets for the definition of the evolution of landslides have been presented and discussed.…”
Section: Landslide Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…This topic has been described by several authors (Dewitte et al, 2008;Turner and Lucieer, 2013;Travelletti et al, 2012;Lucieer et al 2014a;Turner et al, 2015;Marek et al, 2015;Lindner et al, 2016;Peppa et al, 2017). In these works, numerous techniques based on the multi-temporal comparison of RPAS data sets for the definition of the evolution of landslides have been presented and discussed.…”
Section: Landslide Monitoringmentioning
confidence: 99%
“…Westoby et al (2012) emphasized the advantages of RPASs concerning terrestrial laser scanners, which can suffer from line-of-sight issues, and airborne lidar, which are often cost-prohibitive for individual landslide studies. Turner et al (2015) stressed the importance of a good co-registration of multi-temporal DSMs for good results that could decrease in accuracy. The use of benchmarks in areas not affected by morphological changes can be used for a correct calibration of rotational and translation parameters.…”
Section: Landslide Monitoringmentioning
confidence: 99%
“…This landslide affected approximately 250 m of the highway, destroyed two houses, caused the evacuation of 10 others, and delayed the opening of the highway for several months [71]. as, soil erosion [59,60], landslides or rocky surfaces inventory [56,61], landslide detection [62], landslide dynamics and monitoring [57,[63][64][65][66][67], and natural disaster monitoring and evaluation [68,69]. A comprehensive review of remote sensing applications based on UAVs equipped with specific sensor-based technologies has been accomplished to varying degrees across a range of applications.…”
Section: Location Of the Study Areamentioning
confidence: 99%
“…Several recent studies have also demonstrated the power of Structure from Motion algorithms for landslide mapping and monitoring (Niethammer, Rothmund, Schwaderer, Zeman, & Joswig, 2011;Akca, 2013;Lucieer et al, 2014;Nikolakopoulos et al, 2015a;Turner, Lucieer, & De Jong, 2015). Different studies demonstrating the use of UAV data for landslide monitoring have been published (Lin, Tao, Wang, & Huang, 2010;Rau, Jhan, Lob, & Linb, 2011;Turner et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies demonstrating the use of UAV data for landslide monitoring have been published (Lin, Tao, Wang, & Huang, 2010;Rau, Jhan, Lob, & Linb, 2011;Turner et al, 2015).…”
Section: Introductionmentioning
confidence: 99%